Effect of non saturation on the strength and stiffness of a compacted clayey sand - Martins, João (2015)
The present work aims to investigate the influence of compaction water content on the mechanical behavior of a clay sand (SC). A laboratory test campaign was carried out on reconstituted samples of a SC employed in a trial railway embankment. A constant void ratio corresponding to 97% of the modified Proctor was adopted and water content was varied from 4% dry of optimum to 2% wet of optimum. Hydro characterization was conducted through paper filter technique, whereas mechanical behavior characterization was performed through tri-axial consolidated drained tests. A marked influence of molding water content on the mechanical behavior of SC material was found, namely regarding strength and stiffness, which is attributed to suction effect. However, suction effect decreases with increasing stress and strain levels.